2020
DOI: 10.1111/jcmm.15766
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‐148a‐3p in extracellular vesicles derived from bone marrow mesenchymal stem cells suppresses SMURF1 to prevent osteonecrosis of femoral head

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…promoted the expression of cell cycle-related genes, including CDK2, CDK3, CDK4, CCNB, CCNG1, and CCND1, and signi cantly accelerated the cell cycle progression by decreasing the proportion of cells in G0/G1 phase by ow cytometry. The proliferation of bone marrow mesenchymal stem cell and non-smallcell lung cancer can also be promoted by miR-148a-3p mimic [41,42] which consistent with our present research. However, Bao et al and Wang et al have reported that overexpression of miR-148a-3p inhibited the proliferation of gastric cancer cells [43] and diabetic retinopathy cell model [44], respectively.…”
Section: Discussionsupporting
confidence: 89%
“…promoted the expression of cell cycle-related genes, including CDK2, CDK3, CDK4, CCNB, CCNG1, and CCND1, and signi cantly accelerated the cell cycle progression by decreasing the proportion of cells in G0/G1 phase by ow cytometry. The proliferation of bone marrow mesenchymal stem cell and non-smallcell lung cancer can also be promoted by miR-148a-3p mimic [41,42] which consistent with our present research. However, Bao et al and Wang et al have reported that overexpression of miR-148a-3p inhibited the proliferation of gastric cancer cells [43] and diabetic retinopathy cell model [44], respectively.…”
Section: Discussionsupporting
confidence: 89%
“…For example, miR-155-5p was found to be significantly downregulated in ONFH samples [ 16 ]. miR-148a-3p [ 17 ], miR-23b-3p [ 18 ], and miR-26a [ 19 ] were all reported to play a protective role against ONFH. Recent advancement of genome-wide profiling approaches, such as gene microarray and RNA-sequencing technology, enhances the understanding of miRNA and gene expression profiles in the context of ONFH, providing opportunity to identify novel biomarkers and therapeutic targets for ONFH [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is a fascinating question suggesting that understanding the composition of “hypoxic” vs. “normoxic” EVs could provide valuable information on the key regulators of pathologic states. Indeed, identification of microRNA-148a-3p as the mediator of the beneficial effect of BMSC EVs on osteonecrosis confirmed the role of SMURF1 in the pathogenesis [ 132 ]. Similarly, identification of targets of the BMSC EV cargo miRNA-375, that mediate anti-cancer effect on cervical cancer, might reveal further components in the transformation of cervical epithelium [ 92 ].…”
Section: Discussionmentioning
confidence: 96%